Microscopic basis of reaction center modulation in PsbA variants of photosystem II - Sinjini Bhattacharjee; Igor Gordiy; Abhishek Sirohiwal; Dimitrios A. Pantazis (Proceedings of the National Academy of Sciences, 2025)
Photosystem II (PSII) is a protein–pigment complex that utilizes sunlight to catalyze water oxidation and plastoquinone reduction, initiating the electron transfer (ET) cascade in oxygenic photosynthesis. The D1 and D2 proteins are the most important transmembrane subunits of PSII that bind all redox-active components involved in primary charge separation (CS) and ET. D1 is susceptible to oxidative photodamage, particularly under high light, and protection partly involves genetic regulation. Cyanobacterial D1 is encoded by the psbA gene family that expresses distinct isoforms (PsbA1–3) depending on environmental conditions. Most differences in D1 isoforms are close to the active-branch reaction center (RC) pigments P D1 , P D2 , Chl D1 , and Pheo D1 . Here, we combine molecular dynamics simulations with multiscale quantum-mechanics/molecular-mechanics calculations on the membrane-bound PSII monomer of each variant to compare the redox and excited state properties of RC pigments using long-range-corrected density functional theory. We identify specific amino acid substitutions responsible for electrochromic shifts on distinct pigments and pigment groups. Our results indicate that the Pheo D1 acceptor is the primary regulatory target. The redox properties of the Chl D1 –Pheo D1 pair and the energetics of Chl D1 δ+ Pheo D1 δ- charge-transfer states are distinctly modulated in the three isoforms: Compared to the standard psbA 1 , charge separation is inhibited in psbA 2 and facilitated in psbA 3 PSII. The results provide a microscopic description of how genetic variations modulate protein electrostatics and influence primary processes in photosynthetic reaction centers.